The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.4041/kjod.2016.46.5.290
|View full text |Cite
|
Sign up to set email alerts
|

A three-dimensional finite element analysis of molar distalization with a palatal plate, pendulum, and headgear according to molar eruption stage

Abstract: ObjectiveThis study aimed to (1) evaluate the effects of maxillary second and third molar eruption status on the distalization of first molars with a modified palatal anchorage plate (MPAP), and (2) compare the results to the outcomes of the use of a pendulum and that of a headgear using three-dimensional finite element analysis.MethodsThree eruption stages were established: an erupting second molar at the cervical one-third of the first molar root (Stage 1), a fully erupted second molar (Stage 2), and an erup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 43 publications
4
29
0
Order By: Relevance
“…These findings were confirmed by Kang et al and Park et al who reported the displacement distribution level at the compact bone with the headgear lower than the bone-anchored pendulum. 22,34 This was in concurrence with the distal tipping movement that happened with Gerber application, and the bodily movement with the other appliance, and also Lee et al who reported that the high-stress concentration and displacement were obvious around anchorage points. 29 Higher displacement was reported at the PDL of the first molar when compared to other dentition.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…These findings were confirmed by Kang et al and Park et al who reported the displacement distribution level at the compact bone with the headgear lower than the bone-anchored pendulum. 22,34 This was in concurrence with the distal tipping movement that happened with Gerber application, and the bodily movement with the other appliance, and also Lee et al who reported that the high-stress concentration and displacement were obvious around anchorage points. 29 Higher displacement was reported at the PDL of the first molar when compared to other dentition.…”
Section: Discussionsupporting
confidence: 69%
“…Material properties of the components of the dental follicle encompassing the unerupted molar were similar to those of the PDL that had a lower density (►Table 1). 22,23 The contacts between the teeth were postulated to be frictionless. The thickness of the PDL and cortical bone was considered to be 0.2 and 3.4 mm, respectively.…”
Section: Model Components 3d Drawingmentioning
confidence: 99%
“…This is probably a consequence of the poor reliability of methods measuring rotation (1,27). The mesiobuccal rotation of the maxillary first molar has been stated previously, but only one study mentioned rotation of the first mandibular molar, and the rotation was opposite to the present finding during active treatment (18,28). Nonetheless, long-term follow-up revealed stability on molar rotations in their study (18).…”
Section: Mesiopalatal Rotation Of Upper First Molars Has Been Reportementioning
confidence: 61%
“…Recently, Kang et al 27 reported distal tipping and extrusion of the first molar with headgear use in their finite element analysis. On the other hand, the palatal plate resulted in intrusion of the first molar accompanied by more distalization at the root level than at the crown level.…”
Section: Discussionmentioning
confidence: 99%